Enhanced fatigue analysis - incorporating downstream manufacturing processes - Eichlseder, Wilfried (Materiali in tehnologije, 2010)
Most failures of engineering components can be traced back to cyclic loads which cause fatigue of the material. These cyclic loads can be either constantor variable. This influence has to be taken into account in the fatigue analysis, the aim of which is to assure a minimum required lifetime ofa component without breakdown. Simultaneously, a lightweight design is intended by reducing the size of the component. The strength of materials under cyclic loading is essentially lower than those under static loading. However, the cyclic strength is of more importance in practical applications, as more components fail by cyclic loading than by static loads. Regrettably, the strength of cyclic loaded components was discovered relatively late and the first systematic investigations were performed in the 19th century. Cyclic loadings result from mechanic or thermal service loads, which can be superimposed to static loads. When looking at a truck, the chassis is loaded by the dead load of the vehicle. Due to loading and unloading procedures the load is changed into a quasi-static way. Additional cyclic loads emerge during driving operation in addition to the static loads due to braking, acceleration, cornering, or physical conditions just like bumps on the roadwayor air drag. Additional loading is also due to resonance vibrations of engine, gearbox, fuel tank, or the spare wheel. These cyclic loads lead to fatigue of material hence overstraining them to a crack. These cracks propagate and finally lead to failure of the component.
Keywords: utrujenost materialov; trajnost; simulacije; končni elementi